Leituras das regras de escrita de cartas: manual epistolar novo secretario portuguez ou código epistolar como dispositivo de formação pedagógica - Barboza, Kaline Gonzaga (2015)
This master‟s research‟s theme is the education to civility, analyzed by the device of educational formation, the epistolary manual Novo Secretario Portuguez ou Código Epistolar, by JI Roquette, seeking to contribute with the History of Education, highlighting the historical importance of manuals on the constitution of reading and writing formation. The idea of civility is understood as the education of body and soul, for it molds the subject to the social patterns seen as „distinguished‟ in society interaction. Manuals have constituted important devices to education as a way of formation. Also in the Brazilian civilizing project, in which occurred the production, editing and publishing of entire books, exclusively for teaching the writing of letters and with the circulation of models in Paraíba – research scenario and trade evidence copies of epistolary manuals through the sale of ads that title in nineteenth-century newspapers. The research methodology began with reading Novo Secretario Portuguez ou Código Epistolar, considering it‟s been working for centuries and its historical relevance, as a formation device in Brazilians education, establishing strategic ways of how to form a national identity, in the midst of the construction of a modern e civilized country. Another reading took place, through the content and elements of the perigrafia of the epistolary manual, concerning the teaching of how to write letters. This book makes part of the pedagogic press category of education to civility, teaching rules, conduct patters and letter styles for the population, making legit the daily social contact. It‟s noticeable that the act of writing was considered by Roquette as a practice that revealed the subject and his ways as good manners person, distinction object, tuning with values recommended by those times elite. The content in the manual demonstrate that the protocol education also occurred in the way of writing letters, using a proper manual for this intention, using specific cases and personalities examples, chosen as models to be followed. The discussion of the dissertations theme was based in some important theorist that developed studies about civility, books history and epistolary manuals in the international, national e regional scene.